The simulation of dust effects from fragmenting charges. Issue 3 (3rd May 2016) - Soto, Orlando A.; Baum, Joseph D.; Togashi, Fumiya; Löhner, Rainald; Frank, Robert A.; Amini, Ali
Abstract : Purpose: – The purpose of this paper is to determine the reason for the discrepancy in estimated and observed damage caused by fragmenting charges in closed environments. Design/methodology/approach: – A series of carefully conducted physical and numerical experiments was conducted. The results were analyzed and compared. Findings: – The analysis shows that for fragmenting charges in closed environments, dust plays a far larger role than previously thought, leading to much lower pressures and damage. Research limitations/implications: – In light of these findings, many assumptions and results for fragmenting charges in closed environments need to be reconsidered. Practical implications: – This implies that for a far larger class of problems than previously estimated it is imperative to take into consideration dust production and its effect on the resulting pressures. Originality/value: – This is the first time such a finding has been reported in this context.